ChemInform Abstract: Evaluating Dynamic Kinetic Resolution Strategies in the Asymmetric Hydrosilylation of Cyclic Ketimines. Issue 29 (22nd July 2014) - Jones, Simon; Zhao, Peichao
Abstract The dynamic kinetic resolution by HSiCl3‐reduction of cyclic imines is investigated in the presence of an N‐acylated L‐prolinol derived catalyst.